Suicide Prevention Research from Individual to Social Approach - Uludağ, Zeynep; Daşcı, Esra; Keleş, Ali Eşref (Current Approaches in Psychiatry, 2025)
Suicide and self-harm are worldwide problems affecting thousands. There are many reasons and factors to be understood regarding suicide in order to help professionals to intervene before it happens. The studies focusing on individual factors as well as environmental factors need to be well understood in order to be able to make a well-established health policy that is better at preventing suicide. In this review, the concept of suicide, prevalence and prevention of suicide, and the factors related to it have been reviewed. Individualistic and social factors have been taken into account in order to understand the prevention of suicide. Consequently, both an individual and the environment people live in is often important for professionals to understand suicide. Also, the prevalence of suicide might be missing in many cases where people do not report suicide or self-harm related to suicide. Therefore, the screening process must be widened to cover all the people in the area rather than only people who report to the healthcare services. The prevention methods of suicide vary and include both individual approaches and social approaches; therefore, the implication of these various approaches into a prevention intervention seems to be vital. In that regard, education about both mental health problems and suicide, especially for young adults, seems to be effective in preventing suicide. Also, the intersectional approach and social cure for prevention should be considered by professionals for more effective suicide prevention intervention. Lastly, one of the factors seems to be the access to health services in local areas where people feel safe.